Modification of the structure and properties of hardfaced layers with TIG high frequency method - Gucwa, M; Winczek, J; Makles, K; Mičian, M; Yadav, A (IOP conference series. Materials Science and Engineering, 2021)
In this work the investigation is focused on changing the structure and hardness of the surface with high content of carbon and chromium. The use of welding methods to modify the properties of the surface layer allows for optimal use of the properties of materials or changing their properties by differentiate their structure. The surface and structure of hardfaced layers can be improved by additional treatment with another welding arc. The use of the new TIG methods with frequency up to 20000 Hz gives new possibility of the surfacing. The subject of the research were padding welds with the structure of chromium cast iron, which were subjected to the process of remelting the surface layer using the TIG high frequency method. The use of hardfacing and remelting with the TIG method allowed for a noticeable differentiation of the structure, hardness and wear resistance in relation to the initial state.